Guide to genealogy - Resler, Tamara J. (National Geographic Kids, 2018)
Explores what a person's genealogy is and offers a wide range of advice for readers to research their own family history and create a personal family tree, with hands-on activities to do that help readers learn about their families' pasts, and insight into the past history of legal American immigration with immigration records, birth and death certificates, and other legal documents that can help show a genealogy. Includes a glossary.